Agrobacterium mediated callus based transformation protocol for transferring DREB1A gene in wheat (Triticum aestivum L.) - Mehmood, Khalid; Arshad, Muhammad; Ali, Ghulam Muhammad; Razzaq, Abdul; Qureshi, Rehmatullah (Journal of Pure and Applied Agriculture, 2023)
The present study was designed to optimize protocol for transferring DREB1A gene in wheat and selection of one suitable cultivar among Lasani-08, Inqlab-91, Chakwal-97 and GA-02 for the development of transgenic plants. The already optimized callus induction and regeneration media was used for tissue culture. Different treatments of optical density (O.D.), hygromycin, cefotaxime and acetosyringone concentrations were optimized. After optimization of these parameters, the four wheat cultivars were compared with different treatments of infection and co-cultivation time. The Lasani-08 was found to be one of the best cultivars among four cultivars based on the maximum hygromycin resistant calli (18.36%). Its calli were shifted on regeneration media for the development of transgenic plants. The transformed gene was confirmed using gene specific primers through conventional PCR. A lethal dose (50 mg/l) of hygromycin for selection of transformed calli, 300 μM of acetosyringone to enhance transformation process and 500 mg/l cefotaxime to eliminate Agrobacterium after cocultivation, were optimized. The infection time (5 min) and co-cultivation time (48 h) were found to be the most suitable parameters for the maximum transformation efficiency. PCR confirmed that 0.38% of regenerated plants were transgenic. This study will provide a way for transferring other agronomically important genes in wheat cultivars for their improvement.